Physician Knowledge, Attitude, and Experience With Advance Care Planning, Palliative Care, and Hospice: Results of a Primary Care Survey. (August 2013) - Snyder, Sara; Hazelett, Susan; Allen, Kyle; Radwany, Steven
Purpose: To evaluate primary care physicians' understanding of and experience with advance care planning (ACP), palliative care, and hospice and how this might affect their utilization of these services. Methods: Investigator-generated survey. Results: Older age, more years in practice, and more personal and professional experience with ACP were correlated with an increase in the percentage of patients with progressive, chronic life-limiting diseases with whom physicians discussed advance directives. Overall, 97.5% of physician's expressed comfort in discussing ACP yet reported discussing advance directives with only 43% of appropriate patients. Discussion: Often, discussions about ACP or referrals to palliative care or hospice do not occur until the patient is near the end of life. Our results indicate that primary care physician's personal and professional experience with ACP may be contributing to some of the barriers to these discussions.